Tourism Entrepreneurship Business Model: Product and Experience Innovation to Attract Tourists - Fahrurrozi, Muh.; Amrullah, Amrullah; Mohzana, Mohzana; Ramli, Muhammad (Universitas Hamzanwadi, 2024)
The tourism industry in Indonesia, with its diverse culture and natural resources, offers significant potential for economic growth. However, challenges such as intense competition and the need for sustainability demand innovation in tourism entrepreneurship business models. This study aims to explore product innovation and tourist experiences in three major destinations: Bali, Yogyakarta, and Lombok. Employing a descriptive qualitative approach, data were collected through in-depth interviews and observations. The results indicate that the integration of local culture and digital technology enhances the attractiveness of destinations, creating unique experiences for tourists and providing economic benefits to local communities. Although innovation offers numerous advantages, challenges such as limitations in human resources and technological support still need to be addressed to achieve long-term sustainability in the industry. This research fills a gap in the literature by adopting an interdisciplinary approach that encompasses cultural, economic, and technological aspects of tourism entrepreneurship.